2017
DOI: 10.7547/17-144
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships Between Podiatrists and Vascular Surgeons in Building Effective Wound Care Centers

Abstract: This practice memo, a collaborative effort between the Young Physicians' Program of the American Podiatric Medical Association (APMA) and the Young Surgeons Committee of the Society for Vascular Surgery (SVS), is intended to aid podiatrists and vascular surgeons in the early years of their respective careers, especially those involved in the care of patients with chronic wounds. During these formative years, learning how to successfully establish an inter-professional partnership is crucial in order to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Over the course of the past decade, the concept of multidisciplinary "toe and flow" programs has witnessed a remarkable surge in popularity within the medical community, driven by collaborative efforts spearheaded by both podiatrists and vascular surgeons alike [16,22,23]. This noteworthy trend underscores the growing recognition of the benefits that can be reaped from fostering high-level partnerships between these surgical subspecialties.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of the past decade, the concept of multidisciplinary "toe and flow" programs has witnessed a remarkable surge in popularity within the medical community, driven by collaborative efforts spearheaded by both podiatrists and vascular surgeons alike [16,22,23]. This noteworthy trend underscores the growing recognition of the benefits that can be reaped from fostering high-level partnerships between these surgical subspecialties.…”
Section: Discussionmentioning
confidence: 99%
“…These findings add to the growing body of literature describing the benefit of the "limb preservation team" on outcomes of patients with diabetic foot complications and CLI. 11,[16][17][18][19] For example, in a hospital-based limb preservation program, Chung et al reported that amputationfree survival was superior among CLI patients who received multidisciplinary wound care directed by vascular, podiatric, and plastic surgeons compared with those treated by a single surgical service alone. 16 Indeed, in our study, the improved outcomes of patients treated after wound center initiation was likely aided by vascular surgeons making treatment decisions alongside experienced wound care nurses and plastic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The center is thus designed to deliver evidence-based comprehensive wound care, including early evaluation and management of perfusion and ischemia, highfrequency debridements (eg, weekly), aggressive management of infection with the assistance of infectious disease consultants, and advanced wound healing techniques, including skin substitutes and flaps. 10,11 In addition, coordinated care management is a critical component of the AWCC, with integration of additional specialty services (eg, endocrinology, podiatry, foot and ankle surgery), social services, and coordination of inpatient admission as needed. The core elements of the wound center are summarized in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of multidisciplinary teams has been shown to increase overall procedural volume as well as improve limb salvage rates. [60][61][62] Our group has investigated the impact of a multidisciplinary team on limb salvage rates in patients with CLTI. 60 The use of a multidisciplinary team led to significant increases in lower extremity revascularizations and minor amputations, and was associated with a significantly lower rate of major amputations.…”
Section: The Role Of Multidisciplinary Teams In the Care Of Cltimentioning
confidence: 99%